Unseen suffering: Social injustice among women during climate-induced migration in Pakistan - Wahid Ullah; Haijun Dong; Ashfaq Ahmad Shah; Bader Alhafi Alotaibi; Muhammad Khursid; Takaaki Nihei (Climate Risk Management)
Women are highly exposed to climate-induced natural disasters in Pakistan due to socio-cultural barriers resulting in heightened social injustice among them. This paper investigates the drivers of social injustice during forced migration among women living in vulnerable areas of Pakistan. The study utilized data from fifteen key informants’ interviews by employing a systematic narrative analysis to investigate women’s responses towards migration and gender dimensions of adverse climatic events. The results show that economic, socio-cultural, and health related factors were among the key contributors exposing women to social injustice during migration while in search for better life. The findings further unveiled that decisions regarding migration were mainly taken by the household heads especially who in most cases were the male family members. In all circumstances, securing lives, livelihoods, and properties, access to better education, healthcare facilities, and to overall improve socioeconomic situation of the household, were the primary goals of deciding to move to newfound. Given that some members of the household pursue migration as a result of adverse climatic events, government strategies are required to mitigate risks at destinations and create opportunities for the displaced populations.